Avaliação do sistema de aderência entre argamassas colantes no assentamento de piso sobre piso - Fayner Lohany Teixeira de Aguiar (2020)
This work has the general objective of evaluating the adhesion of different brands of adhesive mortars floor to floor when laying ceramic tiles with low porosity, especially porcelain tiles. The adhesion resistance at the interface between the enameled part of the ceramic plate and the back of porcelain tile were also objects of this study. Throught the pullout test, it was found that none of the three mortars reached the resistance recommended by 0,3 MPa, following NBR 13.753 – External or internal floor covering with ceramic plates and using adhesive mortar (ABNT, 1996). With the realization of digital electron microscopic analysis, it was observed that the specimens that showed lower values of adhesion resistance, had less apparent surface porosity and the specimens that presented a greater porosity had a higher performance in terms of adhesion resistance.